2014
DOI: 10.1002/cncr.28802
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative serum methylation levels of TAC1 and SEPT9 are independent predictors of recurrence and survival of patients with colorectal cancer

Abstract: BACKGROUND: Serum carcinoembryonic antigen (CEA) is the only marker recommended for surveillance of colorectal cancer (CRC) recurrence; its sensitivity and specificity, however, are suboptimal. This study sought to evaluate the values of postoperative serum methylation levels of 7 genes for prognostication and especially for recurrence detection after curative resection. METHODS: This prospective cohort study included 150 patients with stage I-III CRC from whom 3 consecutive blood sampling was taken 1 week bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 19 publications
5
71
1
2
Order By: Relevance
“…In‐so‐far as a modest survival benefit with CEA testing as part of a surveillance protocol has been observed , and that the BCAT1/IKZF1 test is more sensitive for recurrence in our study, then definitive studies aimed at assessing potential survival benefit with the BCAT1/IKZF1 test are now indicated. There might also be potential for prediction of prognosis independent of stage, as has been reported for other biomarkers .…”
Section: Discussionmentioning
confidence: 91%
“…In‐so‐far as a modest survival benefit with CEA testing as part of a surveillance protocol has been observed , and that the BCAT1/IKZF1 test is more sensitive for recurrence in our study, then definitive studies aimed at assessing potential survival benefit with the BCAT1/IKZF1 test are now indicated. There might also be potential for prediction of prognosis independent of stage, as has been reported for other biomarkers .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, an increased methylation level of SEPT9 was a predictor of poor prognosis in esophageal squamous cell carcinoma, as well as in prostate cancer on androgen deprivation [52, 53]. Likewise, colorectal cancer patients with high SEPT9 serum methylation levels at 1-year follow-up were found to be at high risk of disease recurrence [64]. Although these promising findings in other cancer entities suggested that aberrant SHOX2 and SEPT9 methylation may also correlate with prognosis in BTC, our results did not confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic impact of ctDNA analysis has been demonstrated in several studies of both localized and metastatic colorectal cancer. In a seminal study, Tie and colleagues detected ctDNA after operation in 20 (8.7 per cent) of 230 patients with stage II colorectal cancer by the Safe‐SeqS NGS method.…”
Section: Clinical Relevance In Gastrointestinal Cancersmentioning
confidence: 99%